Surgical methods in the treatment of basal thumb arthritis – from arthroscopy to arthroplasty - Zoran Sulje; Damir Starčević; Ana Aljinović; Katarina Barbarić Starčević (Acta Clinica Croatica, 2024)
The first carpometacarpal joint is the second most common joint affected by degenerative arthritis. The prevalence of the first carpometacarpal joint arthritis increases with age, especially in postmenopausal women. Ligamentous laxity or injury of the first carpometacarpal joint is thought to be the starting point of development of degenerative changes, accompanied with altered biomechanics of the thumb. As the disease progresses, the joint is destroyed and the thumb and hand function are deteriorating. Although many patients, in different stages of disease, experience pain relief with conservative treatment, surgery is often needed. Decision on the type of surgical procedure depends on the age of the patient, functional demands, and stage of the disease. In early stages of the disease, stabilization of the first carpometacarpal joint, extension osteotomy of the first metacarpal and arthroscopic procedures are used. Th ese are joint-preserving procedures, and they slow down progression of the disease and reduce symptoms. In late stages of the disease, joint arthroplasty procedures and first carpometacarpal arthrodesis are performed. In recent years, late stages of the disease can also be treated arthroscopically. This paper describes different surgical methods, their advantages and drawbacks, with respect to different stages of the disease.